The effect of TIG welding technology parameters on the weld quality of copper material joints for heat pipe applications - Azwinur, Azwinur; Kusuma, M. Hadi; Usman, Usman; Dharma, Surya (Jurnal Polimesin, 2024)
Copper is a commonly used material for heat pipe fabrication using the welding process. However, welding copper to copper presents significant challenges due to its inherent material properties. Its exceptionally high thermal conductivity facilitates rapid heat dispersion, complicating the maintenance of a stable melting zone. Furthermore, copper is prone to oxidation, which generates brittle oxides that can adversely affect weld quality. This research paper examines the relationship between TIG welding parameters—specifically current, voltage, shielding gas flow rate, and filler rods—and the mechanical properties of the resulting heat pipe material. The study involves varying the welding current at levels of 120 A, 135 A, and 150 A, along with different types of filler rods. The results indicate that both the selection of welding current and the type of filler rod significantly influence the tensile strength of copper welded joints. Notably, the use of higher currents in ERCuSi-A welding tends to decrease hardness in the HeatAffected Zone (HAZ), while producing more complex variations in hardness within the Weld Metal (WM), dependent on the interplay between heat and the chemical composition of the filler rod. Additionally, nickel in the ERCuNi filler rod contributes to an increase in weld hardness.